PENGARUH UKURAN BILAH KAYU SENGON TERHADAP BEBERAPA SIFAT PAPAN BlOK - l M Sulastiningsih; Paribotro Sutigno; M l Iskandar (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Experimental blockboards (5-ply)were made of sengon wood (Earaserianthes falcataria) glued with urea formaldehyde. Thickness of veneers were 2 mm for face and back layers and 3 mm for cross core layer. The dimension of strip (core layer) divided into two different thickness (I cm and 1.5 cm) and three different width (0.7 cm; 2.5 cm and 7.6 cm). The blockboard properties were tested according to the Indonesian Standard (SNI), Japanese Standard (JAS) and Germany Standard (DIN) included moisture content, density, bending strength, moisture resistant bonding strength and delamination. The objective of this study was to determine the effect of strip dimension on some properties of sengon blockboard.The result revealed that the average density of sengon blockboard was 0.33 g/m3. The width of strip affected the thickness swelling and the length expansion of sengon blockboard but the width expansion. The thickness of strip affected the width and length expansions however did not affect the thickness swelling of sengon blockboard. The moisture resistant bonding strength of sengon blockboard with all treatments based on tensile strength and delamination tests met the SNI and JAS requirements. Compared with DIN Standard the sengon blockboard that met the bending strength requirement only that made of strip with 0. 7 cm in width and 1 cm thick. Indonesian Standard for blockboard does not require bending strength test.